Academician Ion of Gheorghe Sbiera in the Century of the Revival of the National Conscience of Romanians from Bukovina - Pintilia Elena (Annals of Philosophy, Social and Human Disciplines, 2018)
The study highlights the fundamental contribution of the cultural activity of the academician Ioan of Gheorghe Sbiera , to the establishment of the cultural and national unity of the Romanians in Bukovina in the second half of the 19th century. The Bucovinean scholar was a brilliant philologist, literary historian, editor, memorialist, folklorist and, last but not least, historian. He is awarded the title of the first professor of the Romanian Language and Literature Department at the University of Cernăuţi, from which he taught the first course in Romanian, although he was forbidden by the foreign authorities. As a founding member of the Romanian Academy, it is worthwhile to be considered the first philologist to present the first full and homogeneous version of the Latin alphabet of the Romanian language. His entire activity brings a valuable contribution to the history of the Romanians in Bukovina, definitively putting his mark on the evolution of the stages preceding the Union in 1918.